Pemahaman Dan Pengetahuan Tentang Bantuan Hidup Dasar Pada Siswa Kelas XII SMA IT IQRA Bengkulu - Rustandi, Handi; Sofais, Danur Aziza R.; Suryanto, Jipri; Nuh, Yalta Muhammad; Tranado, Hengki (Jurnal Dehasen Mengabdi, 2023)
Teenagers, especially students at the senior high school level (SMA) should be able to carry out cardiopulmonary resuscitation properly. The purpose of this service is to provide understanding and knowledge about basic life support to class XII students of SMA ITIDRA Bengkulu. After evaluating through mentoring training the target audience's knowledge about how to handle people who need basic life support measures, the average knowledge before taking action or understanding is not good. However, after providing an understanding of basic life support knowledge the level of knowledge of class XII students increases . The participants were enthusiastic about this training activity because they gained new knowledge about handling people who needed basic life support measures in the community and their immediate family.